Nursing Management of Patients with HHD, Cardiac Shock, Pleural Effusion, and Electrolyte Imbalance in the High Care Unit - Niken Ambarwati; Ristina Mirwanti; Ayu Prawesti Priambodo (Utami Publisher, 2026)
The Hypertensive Heart Disease (HHD) is a chronic condition that arises from uncontrolled hypertension, resulting in myocardial damage and ventricular dysfunction that can increase the risk of cardiogenic shock. Pleural effusion occurs because of cardiac congestion and causes fluid buildup in the pleural cavity. In patients with this condition, unstable electrolyte levels are often found in the body. The combination of hypertensive heart disease, cardiogenic shock, pleural effusion, and electrolyte disturbances is a complex problem, requiring a multidisciplinary approach to prevent fatal complications such as multisystem failure and risk of death. This case report aims to describe nursing management in patients with hypertensive heart disease, cardiogenic shock, pleural effusion, and electrolyte disturbances, then relate it to scientific evidence through a literature review. The method used in this study was a case report. The subject of this case report was a 65-year-old woman with hypertensive heart disease, cardiogenic shock, pleural effusion, and electrolyte disturbances in the High Care Unit. Nursing management of patients with hypertensive heart disease, cardiogenic shock, pleural effusion, and electrolyte disturbances includes comprehensive assessment, collaborative intervention in the administration of inotropics, fluid management, oxygenation management, and collaboration in pleural puncture, as well as evaluation. Patients with hypertensive heart disease, cardiogenic shock, pleural effusion, and electrolyte disturbances present complex problems that can lead to death if not treated quickly and appropriately. Nurses play a major role in nursing management through assessment, problem identification, intervention, and periodic evaluation of hemodynamic status, fluid balance, and patient response to therapy.